2018
DOI: 10.1111/cbdd.13177
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of pyridinium‐hydrazone derivatives as potential antitumoral agents

Abstract: The hydrazones of 4-hydrazinylpyridinium bearing alkylphenyl groups on pyridinium nitrogen were synthesized and evaluated for their cytotoxic activity against MCF-7, PC3, U2OS, and HEK293 cell lines by Wst1 cell proliferation assay. Cytotoxic activity results indicated that d derivatives having butylene chain; 4 and 5 series having naphthalene and anthracene ring systems showed high cytotoxic activity (IC = 3.27-8.54 μm) on cancer cells. 3d (4-(2-(4-hydroxybenzylidene)hydrazinyl)-1-(4-phenylbutyl)pyridinium br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Based on the literature survey, the synthesis of hydrazide/hydrazone derivatives with various functional groups was considered by medicinal chemists worldwide. These derivatives possessed a variety of biological activities, comprising antimicrobial (Takaji et al 1997;Khattab et al 2016;Popiołek 2017;Haiba et al 2019;Popiołek, Rysz, et al 2020;Popiołek, Patrejko, et al 2020;Rohane et al 2020Rohane et al ), antiviral (S ßenkardes ß et al 2016Wang et al 2018), antiparasite (Coimbra et al 2019;Tahghighi et al 2020) and anticancer (Tantak et al 2017;Nasr et al 2018;Parlar et al 2018;Popiołek, Patrejko, et al 2020) activities, which confirmed their considerable potential for new drug development. On the other hand, some quinoline derivatives containing hydrazide/hydrazone and other moieties were claimed to have suitable antibacterial (Ajani et al 2018), anticancer (Katariya et al 2020;Puskullu et al 2020), antifungal (El Shehry et al 2018Reginatto et al 2021) and antiparasitic (Bhat et al 2012;Coimbra et al 2013;Tahghighi et al 2020) activities.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on the literature survey, the synthesis of hydrazide/hydrazone derivatives with various functional groups was considered by medicinal chemists worldwide. These derivatives possessed a variety of biological activities, comprising antimicrobial (Takaji et al 1997;Khattab et al 2016;Popiołek 2017;Haiba et al 2019;Popiołek, Rysz, et al 2020;Popiołek, Patrejko, et al 2020;Rohane et al 2020Rohane et al ), antiviral (S ßenkardes ß et al 2016Wang et al 2018), antiparasite (Coimbra et al 2019;Tahghighi et al 2020) and anticancer (Tantak et al 2017;Nasr et al 2018;Parlar et al 2018;Popiołek, Patrejko, et al 2020) activities, which confirmed their considerable potential for new drug development. On the other hand, some quinoline derivatives containing hydrazide/hydrazone and other moieties were claimed to have suitable antibacterial (Ajani et al 2018), anticancer (Katariya et al 2020;Puskullu et al 2020), antifungal (El Shehry et al 2018Reginatto et al 2021) and antiparasitic (Bhat et al 2012;Coimbra et al 2013;Tahghighi et al 2020) activities.…”
Section: Introductionmentioning
confidence: 85%
“…2018; Parlar et al . 2018; Popiołek, Patrejko, et al . 2020) activities, which confirmed their considerable potential for new drug development.…”
Section: Introductionmentioning
confidence: 99%
“…16 Hydroxychloroquine (HCQ) is an autophagy inhibitor and a derivative of the antimalaria chloroquine (CQ), but with the addition of a hydrazone. 15 Wolpin et al conducted clinical trials using HCQ in 20 patients with metastatic pancreatic cancer that did not respond to chemotherapy. 17 Patients received 400 or 600 mg of HCQ twice daily.…”
Section: Anticancer Applicationsmentioning
confidence: 99%
“…In cancer tissue, autophagy, which removes misfolded proteins and damaged organelles, suppresses the initiation of tumor growth in the early stages of cancer or allows longer survival times in later stages. 15 Because most tumors depend on the autophagy pathway to replenish nutrient homeostasis from the degraded proteins, lipids, and carbohydrates, autophagic inhibitors have been recently investigated as a new form of cancer therapy. 16 Hydroxychloroquine (HCQ) is an autophagy inhibitor and a derivative of the antimalaria chloroquine (CQ), but with the addition of a hydrazone.…”
Section: Applications Of Hydrazonesmentioning
confidence: 99%
“…Hydrazine and their derivatives are a series of highly active organic molecules [8]. They have important biological activities and this functional groups are found as a core structure in many chemotherapeutic agents having antimicrobial, antimalarial, antileishmanial, antiviral and anticancer effects [9].…”
Section: Introductionmentioning
confidence: 99%